The formation of bachelors’ digital competencies at the university - Tsarapkina, Julia M. (2020)
The development of modern information and communication technologies leads to the emergence of new requirements for the preparation of bachelors of higher educational institutions. These requirements justify the need for digital competencies. The process of their formation in the conditions of informatization of vocational education is of high importance. Digital competencies contribute to the creativity of thinking, an initiative in achieving goals, the formation of cognitive skills, including a focus on self-development and achieving high results, increasing the competitiveness of the bachelor in the labor market. The purpose of the article is to analyze the experience of the formation of digital competencies of bachelors by higher educational institutions. These competencies represent the ability and willingness to use electronic educational resources for educational and professional activities. Digital competencies are based on computer literacy and the independence of digital tools. Digital competencies reflect the use of digital teaching aids - a set of methods and technologies used in digital didactics. New electronic tools were introduced into the educational process, which was used by students in carrying out professional activities. Electronic technologies were used as the main and additional educational materials in the organization of individual and group work.